Cardiac contractility is a key factor in determining pulse pressure and its peripheral amplification - Piccioli, Francesco; Li, Ye; Valiani, Alessandro; Caleffi, Valerio; Chowienczyk, Phil; Alastruey, Jordi (Frontiers in Cardiovascular Medicine, 2023)
Background: Arterial stiffening and peripheral wave reflections have been considered the major determinants of raised pulse pressure (PP) and isolated systolic hypertension, but the importance of cardiac contractility and ventricular ejection dynamics is also recognised. Methods: We examined the contributions of arterial compliance and ventricular contractility to variations in aortic flow and increased central (cPP) and peripheral (pPP) pulse pressure, and PP amplification (PPa) in normotensive subjects during pharmacological modulation of physiology, in hypertensive subjects, and in silico using a cardiovascular model accounting for ventricular–aortic coupling. Reflections at the aortic root and from downstream vessels were quantified using emission and reflection coefficients, respectively. Results: cPP was strongly associated with contractility and compliance, whereas pPP and PPa were strongly associated with contractility. Increased contractility by inotropic stimulation increased peak aortic flow (323.9±52.8 vs 389.1±65.1 ml/s), and the rate of increase (3193.6±793.0 vs 4848.3±450.4 ml/s2) in aortic flow, leading to larger cPP (36.1±8.8 vs 59.0±10.8 mmHg), pPP (56.9±13.1 vs 93.0±17.0 mmHg) and PPa (20.8±4.8 vs 34.0±7.3 mmHg). Increased compliance by vasodilation decreased cPP (62.2±20.2 vs 45.2±17.8 mmHg) without altering dP/dt, pPP or PPa. The emission coefficient changed with increasing cPP, but the reflection coefficient did not. These results agreed with in silico data obtained by independently changing contractility/compliance over the range observed in vivo. Conclusions: Ventricular contractility plays a key role in raising and amplifying PP, by altering aortic flow wave morphology.